The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/1474022219844986
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the emotional journey of the doctoral ‘hero’: Challenges faced and breakthroughs made by creative arts and humanities candidates

Abstract: This article discusses how doctoral candidates identify and navigate personal learning challenges on their journey to becoming researchers. Our study asked creative arts and humanities candidates to think beyond the research project itself and reflect on emotional hurdles they were facing or had overcome. The findings point to a great deal of ‘invisible’ work that underpins doctoral study, and show that such hidden work can have a major influence not only on the research project, but also on progress and satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…This collaboration extended well beyond the twoday workshop as students developed further, tangible, outcomes in the form of published book chapters and in critiquing and editing groups. These book chapters engage with many of the invisible and multidimensional aspects of doctoral study identified in this research, and provide guidance for students that may assist them plan forand respond tothe emotional and intellectual challenges involved (Batty et al, 2019;Brien et al, 2019).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This collaboration extended well beyond the twoday workshop as students developed further, tangible, outcomes in the form of published book chapters and in critiquing and editing groups. These book chapters engage with many of the invisible and multidimensional aspects of doctoral study identified in this research, and provide guidance for students that may assist them plan forand respond tothe emotional and intellectual challenges involved (Batty et al, 2019;Brien et al, 2019).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Usually, this type of training may take the form of events and workshops, mentoring schemes, peer-to-peer groups (for example, writing groups or journal clubs), or industry internships. This training can be expensive and often generic, with little capacity to ensure quality and consistency across the country (Batty et al, 2019). Although some sector-wide training consultancy programmes exist [1], most research training is delivered by the Graduate Research divisions with little specific input from supervisory teams [2].…”
Section: Background and Contextmentioning
confidence: 99%
“…Highlighting these social dimensions of writing in the academy enables us, as writeracademics, to acknowledge the key roles that collaboration and community-building play in our scholarly work. Many scholars also agree that HDR students in particular benefit enormously from being part of communities of practice, where they are encouraged to form professional networks, can access feedback and also gain the social benefits of feeling part of a community (for example, see Batty et al 2019). Communities of practice are important places of negotiation, learning, meaning-making, and the development of identity (Wenger 1998: 72) and offer a 'mode of belonging' (Wenger 2000: 227) which is vital to HDR students as they begin to develop their scholarly profile and establish professional relationships.…”
Section: Connection Discussion Reflection: Collaborating On Traditional Research In the Field Of Creative Writingmentioning
confidence: 99%
“…For students of disciplines such as creative writing, feelings of isolation are heightened as collaborative research is less common for them than it is for their counterparts in disciplines such as the experimental sciences (Fisher 2006: 41), and very few people outside the discipline understand the unique challenges of completing practice-led research while working to maintain a creative practice that is separate from the research. Creative writing candidates sometimes struggle to step away from their practice in order to 'up-skill in research' (Batty et al 2020: 359) and can struggle 'with the shift in gear from intuitive making/doing to research-based planning, doing/making and reflection (Carter 2004in Batty et al 2020. 'Isolation,' Fisher says, 'can be the factor most likely to lead to long completion times, or even failure to complete ' (2006: 42).…”
Section: Literature Reviewmentioning
confidence: 99%